Correlation of Corrosion and Biomechanics in the Retrieval of a Single Modular Neck Total Hip Arthroplasty Design - Lanting, Brent A.; Teeter, Matthew G.; Vasarhelyi, Edward M.; Ivanov, Todor G.; Howard, James L.; Naudie, Douglas D.R. (The Journal of arthroplasty, 2015)
Increased modularity of total hip arthroplasty components has occurred, with theoretical advantages and disadvantages. Recent literature indicates the potential for elevated revision rates of modular neck systems and the potential for local pseudotumor and metallosis formation at the modular neck/stem site. Retrieval analysis of one modular neck implant design including SEM (SCANNING ELECTRON MICROSCOPY) assessment was done and correlated with FEA (finite element analysis) as well as clinical features of patient demographics, implant and laboratory analysis. Correlation of the consistent corrosion locations to FEA indicates that the material and design features of this system may result in a biomechanical reason for failure. The stem aspect of the modular neck/stem junction may be at particular risk.